Is the prevalence of adult asthma and allergic rhinitis still increasing? Results of an Italian study - Verlato, Giuseppe; Corsico, Angelo; Villani, Simona; Cerveri, Isa; Migliore, Enrica; Accordini, Simone; Carolei, Adriana; Piccioni, Pavilio; Bugiani, Massimiliano; Cascio, Vincenzo Lo; Marinoni, Alessandra; Poli, Albino; et al. (Journal of Allergy and Clinical Immunology, 2003)
Background: The prevalence of asthma and allergic rhinitis has increased worldwide during the 1970s and 1980s. Objective: This study was aimed at evaluating whether the increasing trend in prevalence persisted during the 1990s in the young adult Italian population. Methods: In 1998 to 2000 a screening questionnaire was sent by mail to a general population sample aged 20 to 44 years; nonresponders were contacted again first by mail and then by phone, achieving a final response rate of 78.1% (6876 of 8800). Prevalence estimates, adjusted to correct for nonresponse bias, were compared with those recorded in Italy in 1991 to 1993 during the European Community Respiratory Health Survey, when response rate had been slightly higher (87.6%). Temporal variations in symptom prevalence were analyzed by a logistic regression model, controlling for sex, age, site of residence (urban vs suburban areas), season of response, response rate, and type of contact (mail vs phone). Results: The prevalence of asthma attacks did not vary significantly from 1991 to 1993 (3.6%) to 1998 to 2000 (3.2%) (P = .188). The prevalence of asthma-like symptoms (wheezing, chest tightness, shortness of breath) tended to decrease in the age classes of 32.5 to 45 years, while increasing in the youngest age class (20 to 26 years). A clear-cut increase from 15.4% to 18.3% was observed for the prevalence of allergic rhinitis (P < .001), whereas the proportion of people under antiasthmatic treatment increased in suburban areas but not in urban areas (interaction time–site of residence, P < .001). Conclusion: Asthma prevalence has not increased during the last decade in Italy. The persistence of an increasing trend in allergic rhinitis prevalence deserves attention. (J Allergy Clin Immunol 2003;111:1232-8.)